Priority: safe working conditions - Jolanta Skowroń (Nofer Institute of Occupational Medicine, 2019)
The drawing up of a new regulation of the Minister of Family, Labour and Social Policy regarding the maximum admissible concentrations and intensities of agents harmful to health in the working environment resulted from the obligatory implementation into national law the provisions of Commission Directive (EU) 2017/164 of 31 January 2017 establishing a fourth list of indicative occupational exposure limit values pursuant to Council Directive 98/24/EC, and amending Commission Directives 91/322/EEC, 2000/39/EC and 2009/161/EU, the provisions of which Member States had to introduce by 21 August 2018, and partly Directive 2017/2398/EU of the European Parliament and of the Council of 12 December 2017 amending Directive 2004/37/EC on the protection of workers from the risks related to exposure to carcinogens or mutagens at work. The Regulation takes into account 13 applications submitted in the years 2014−2017 by the Interdepartmental Commission for Maximum Admissible Concentrations and Intensities for Agents Harmful to Health in the Working Environment to the minister competent for labour issues. The Commission was appointed by way of the regulation of the Prime Minister of 15 December 2008 (Journal of Laws 2015, item 1772, as amended), and its tasks include submitting to the minister competent for labour issues applications regarding the value of the maximum admissible concentrations and intensities for agents harmful to health in the working environment. Med Pr. 2019;70(4):497-509